2019
DOI: 10.1080/19476337.2019.1571530
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and bioactive characteristics of Ayocote bean (Phaseolus coccienus L.): An underutilized legume harvested in Mexico

Abstract: Nutritional composition, content of phenolic compounds and antioxidant properties of the four Mexican varieties of Ayocote beans (Phaseolus coccineus L.) were studied. Ayocote beans were found to be a promising source of proteins, carbohydrates, fibre and minerals. Sucrose (55.6-62.2 g/kg) and stachyose (24-24.4 g/kg) were considered as the major sugar and oligosaccharide, respectively. Glutamic acid was the most abundant amino acid (32.2 to 35.8 g/kg), while cysteine was present at the lowest concentration (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 48 publications
6
26
1
1
Order By: Relevance
“…The species that showed significant differences were P. coccineus and P. polyanthus with P. lunatus, and with P. vulgaris (Figure 3). Similar results were reported when P. coccineus accessions were compared with P. vulgaris accessions, where a higher concentration of polyphenols, flavonoids, anthocyanins, and even higher antioxidant activity was found in the accessions exhibiting purple, black, and brown colors [18,21].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The species that showed significant differences were P. coccineus and P. polyanthus with P. lunatus, and with P. vulgaris (Figure 3). Similar results were reported when P. coccineus accessions were compared with P. vulgaris accessions, where a higher concentration of polyphenols, flavonoids, anthocyanins, and even higher antioxidant activity was found in the accessions exhibiting purple, black, and brown colors [18,21].…”
Section: Discussionsupporting
confidence: 86%
“…Meanwhile, the CH-16 accession has 2.4% less protein than another purple variety (21.9%) of P. coccineus [17]. In addition to the variation between species and between varieties of the same species, other factors such as fertilizer use, agricultural practices, and soil-climate characteristics of cultivation sites can influence the protein content of bean seeds [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Legumes, a major food of the human diet, may contribute to some of the health benefits associated with this eating pattern. Their health benefits include a low saturated fat content, high content of essential nutrients, richness in important micronutrients (including potassium, magnesium, folate, iron, and zinc) [20] and bioactive compounds [21]. They are responsible for different antioxidant, anticarcinogenic, anti-inflammatory, antidiabetic activities, etc.…”
Section: Discussionmentioning
confidence: 99%
“…They are responsible for different antioxidant, anticarcinogenic, anti-inflammatory, antidiabetic activities, etc. [21]. Previous studied have reported that sprouts, leaves and seeds of soybean and mung bean contain high amounts of crude proteins, amino acids, lipids and minerals [22][23][24].…”
Section: Discussionmentioning
confidence: 99%